Surgical evaluation in children <3 years of age with drug‐resistant epilepsy: Patient characteristics, diagnostic utilization, and potential for treatment delays. Issue 1 (15th November 2021) - Perry, Michael Scott; Shandley, Sabrina; Perelman, Max; Singh, Rani K.; Wong‐Kisiel, Lily; Sullivan, Joseph; Gonzalez‐Giraldo, Ernesto; Romanowski, Erin Fedak; McNamara, Nancy A.; Marashly, Ahmad; Ostendorf, Adam P.; Alexander, Allyson; et al.
Abstract: Objective: Drug‐resistant epilepsy (DRE) occurs at higher rates in children <3 years old. Epilepsy surgery is effective, but rarely utilized in young children despite developmental benefits of early seizure freedom. The present study aims to identify unique patient characteristics and evaluation strategies in children <3 years old who undergo epilepsy surgery evaluation as a means to assess contributors and potential solutions to health care disparities in this group. Methods: The Pediatric Epilepsy Research Consortium Epilepsy Surgery Database, a multicentered, cross‐sectional collaboration of 21 US pediatric epilepsy centers, collects prospective data on children <18 years of age referred for epilepsy surgery evaluation. We compared patient characteristics, diagnostic utilization, and surgical treatment between children <3 years old and those older undergoing initial presurgical evaluation. We evaluated patient characteristics leading to delayed referral (>1 year) after DRE diagnosis in the very young. Results: The cohort included 437 children, of whom 71 (16%) were <3 years of age at referral. Children evaluated before the age of 3 years more commonly had abnormal neurological examinations ( p = .002) and daily seizures ( p = .001). At least one ancillary test was used in 44% of evaluations. Fifty‐nine percent were seizure‐free following surgery ( n = 34), with 35% undergoing limited focal resections. Children with delayed referrals more often had focal aware ( p < .001) seizures and recommendation for palliative surgeries ( p < .001). Significance: There are relatively few studies of epilepsy surgery in the very young. Surgery is effective, but may be disproportionally offered to those with severe presentations. Relatively low utilization of ancillary testing may contribute to reduced surgical therapy for those without evident lesions on magnetic resonance imaging. Despite this, a sizeable portion of patients have favorable outcome after focal epilepsy surgery resections.